2011
DOI: 10.1021/jf103977q
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation Stability of Folic Acid in Powder and Aqueous Solution

Abstract: This study attempts to examine the folic acid stability after irradiation treatment, under different physical states, pH values, and atmosphere conditions. Aqueous folic acid samples, folic acid in powder, and wheat flour fortified with folic acid were irradiated by an electron beam (E-beam) between 0 (control) and 10.0 kGy. It was realized that the physical state of folic acid plays an important role on its stability toward E-beam processing, being largely unstable in solution, no matter the pH and atmosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…Radiation doses over 1 kGy degraded intensely FA molecule into more polar fragments. These results are in accordance with others studies on FA radio-stability (Araújo et al, 2011;Araújo et al, 2012;El-Dessouky et al, 1988;Kesavan et al, 2003). During the development of the proposed LC/UV method, gradient conditions were optimized including an increase of organic phase (MeOH) concentration up to 100%.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Radiation doses over 1 kGy degraded intensely FA molecule into more polar fragments. These results are in accordance with others studies on FA radio-stability (Araújo et al, 2011;Araújo et al, 2012;El-Dessouky et al, 1988;Kesavan et al, 2003). During the development of the proposed LC/UV method, gradient conditions were optimized including an increase of organic phase (MeOH) concentration up to 100%.…”
Section: Resultssupporting
confidence: 87%
“…In addition, the consumers are concerned about the food they eat and ask for more assurances on the quality, the safety and the geographical origin of the products that they consume (Di Stefano et al, 2012). Despite few reports on FA radio-degradation found in literature (Araújo et al, 2011;El-Dessouky, Abd-Elwahab, & Turk, 1988;Kesavan, Pote, Batra, Viswanathan, 2003;Nakken & Pihl, 1966) much is still let to be known, specially on the mechanism of FA radiolysis. The purpose of the present work is to identify and quantify by HPLC the radio-degradation products of folic acid aqueous solutions submitted to increasing doses of ionizing radiation and to investigate the possible radio-degradation mechanism of this vitamin.…”
Section: Introductionmentioning
confidence: 96%
“…Araújo et al (2011) found that folic acid is much less stable to irradiation in aqueous form compared with the powdered form. However, the combination of the high moisture content of masa and high masa holding temperatures prior to baking is a likely cause of chemical degradation.…”
Section: Resultsmentioning
confidence: 99%
“…However, the combination of the high moisture content of masa and high masa holding temperatures prior to baking is a likely cause of chemical degradation. Araújo et al (2011) found that folic acid is much less stable to irradiation in aqueous form compared with the powdered form. The moisture content (w/w) of all masa samples ranged from 56 to 61% (58.3 ± 1.2).…”
Section: Resultsmentioning
confidence: 99%
“…In PLE systems, optimization studies generally start with determining of suitable solvent or solvent mixture and is usually followed by the same solvent in subsequent extraction operations. Buffers, diluted acids, diluted alkali, water, phosphate buffer (pH 8-9), ammonium acetate, ammonium hydroxide or other polar solvents are used often for recovery of a wide range of folic acid from diverse sample types including multivitamin, wheat flour, fortified cereal products, fruit juice, baby foods, infant milk, blood and vegetables [24][25][26]. Table 1 summarizes all optimized parameters in PLE.…”
Section: Ple Extraction Parametersmentioning
confidence: 99%